Capacitive Deionization for the Removal of Paraquat Herbicide from Aqueous Solution - Tusekile Alfredy; Joyce Elisadiki; Yusufu Abeid Chande Jande (Adsorption Science & Technology)
In comparison to other conventional methods like adsorption and reverse osmosis (RO), capacitive deionization (CDI) has only been investigated extensively for the removal of inorganic pollutants from water, demonstrating limited practicality. Herein, the study investigated the use of CDI for the removal of paraquat (PQ) herbicide from water by using commercial activated carbon (AC) electrodes. The CDI performance was examined as a function of the initial PQ concentration, applied voltage, flowrate, treatment time, and cycle stability testing in the batch mode approach. The applied voltage had a beneficial effect on the removal efficiency, whereas the removal efficiency of PQ declined as the initial PQ concentration increased. However, the electrosorption capacity gradually increased with the increase of initial feed solutions’ concentration. The maximum removal efficiency and electrosorption capacity achieved at 5 mg/L and 20 mg/L PQ initial concentrations, an applied voltage of 1.2 V, and 5 mL/min flowrate were 100% and 0.33 mg/g and 52.5% and 0.7 mg/g, respectively. Washing the electrodes with distilled water achieved sequential desorption of PQ, and the process produces a waste stream that can be disposed of or treated further. Therefore, the CDI method is considered a promising and efficient method for removing organic pollutants from water including pesticides.